Analisis Kondisi Sosial Ekonomi Keluarga dan Dampaknya Terhadap Perilaku Bullying - Rani Sofya; Ananda Maha Putri; Rizki Syafril; Tri Kurniawati; Mentari Ritonga; Nita Sofia (Universitas Negeri Padang, 2023)
This study explains the association between children's bullying behavior and socioeconomic conditions. The prevalence of bullying occurrences and the need to learn more about the connection between bullying behavior and socioeconomic status are the driving forces behind this study. A sample of 64 parents and guardians of pupils in Nagari Tanjung Sani, Tanjung Raya District, Agam Regency, participated in this study. Based on the study's findings, it was discovered that 31.9% of kids from work and farming households had been the victims of emotional, verbal, or physical bullying.